PROLACTIN AS A HORMONE RESPONSIVE TO PHYSICAL EXERCISE - Wiktoria Skowron; Mateusz Kalita; Marcel Bobiński; Justyna Bartol; Klaudia Romejko; Justyna Rajczyk; Monika Wiczuk-Wiczewska; Zuzanna Wieczorek; Adam Szymczak; Aleksandra Kozińska (International Journal of Innovative Technologies in Social Science, 2025)
Background. Physical exercise is a major physiological stressor that affects the human endocrine system. Among the hormones responsive to physical exertion is prolactin (PRL), known primarily for its role in lactation but also involved in stress regulation, immune function, metabolism, and reproduction.Aim. This article aims to review current knowledge on the effects of intense physical activity on prolactin levels and the potential consequences for hormonal balance in athletes.Material and methods. A systematic literature review was conducted using PubMed and Scopus databases. Inclusion criteria were English-language articles with full-text access, including original and review papers analyzing prolactin changes in response to exercise in humans. A total of 183 publications were screened, and those not meeting the methodological or thematic criteria were excluded.Results. Intense physical exercise, particularly above the anaerobic threshold (e.g., HIIT), causes a sharp and transient increase in prolactin levels, with the response magnitude influenced by exercise intensity, duration, and environmental factors. Regular training may modulate both baseline prolactin levels and acute hormonal responses. Differences based on sex, training status, and menstrual cycle phase were also observed. Prolactin’s rise post-exercise may contribute to metabolic adaptation, immune modulation, and recovery processes. However, chronically elevated PRL levels—common in overtrained individuals—can negatively affect reproductive and metabolic health.Conclusions. Prolactin plays a broader physiological role than previously appreciated. Its exercise-induced elevation reflects the integration of neuroendocrine and immune responses to physical stress. Understanding this hormonal response is essential in optimizing training protocols, supporting recovery, and preventing endocrine dysfunction in athletes.